Transcriptome Profiling of Tomato Fruit Development Reveals Transcription Factors Associated with Ascorbic Acid, Carotenoid and Flavonoid Biosynthesis - Ye, Jie (PLoS One, 2015)
Tomato (Solanum lycopersicum) serves as a research model for fruit development; however, while it is an important dietary source of antioxidant nutrients, the transcriptional regulation of genes that determine nutrient levels remains poorly understood. Here, the transcriptomes of fruit at seven developmental stages (7, 14, 21, 28, 35, 42 and 49 days after flowering) from two tomato cultivars (Ailsa Craig and HG6-61) were evaluated using the Illumina sequencing platform. A total of 26,397 genes, which were expressed in at least one developmental stage, were detected in the two cultivars, and the expression patterns of those genes could be divided into 20 groups using a K-mean cluster analysis. Gene Ontology term enrichment analysis indicated that genes involved in RNA regulation, secondary metabolism, hormone metabolism and cell wall metabolism were the most highly differentially expressed genes during fruit development and ripening. A co-expression analysis revealed several transcription factors whose expression patterns correlated with those of genes associated with ascorbic acid, carotenoid and flavonoid biosynthesis. This transcriptional correlation was confirmed by agroinfiltration mediated transient expression, which showed that most of the enzymatic genes in the ascorbic acid biosynthesis were regulated by the overexpression of each of the three transcription factors that were tested. The metabolic dynamics of ascorbic acid, carotenoid and flavonoid were investigated during fruit development and ripening, and some selected transcription factors showed transcriptional correlation with the accumulation of ascorbic acid, carotenoid and flavonoid. This transcriptome study provides insight into the regulatory mechanism of fruit development and presents candidate transcription factors involved in secondary metabolism.